Noncontigous cervical and lumbar vetebral tuberculosis - Dulanto, Ana Luz (2019)
A 35 year-old woman with chronic neck pain for two years and with fever and cervical adenomegaly in the last five weeks. The lymph node aspirate was acid fast bacili (+). The images showed collapse of vertebra L2, spondylodiscitis L2-L3 and paravertebral abscesses. The patient’s pain and fever improved with TB treatment.